Time Is on My Side: Relational Contracts and Aggregate Welfare - Bohdan Kukharskyy; Michael P. Pflüger (Institute of Labor Economics (IZA), 2018)
This paper develops a simple general equilibrium model which establishes a link between the patience of economic agents and the well-being of nations. We show that firms in long-term oriented countries can mitigate hold-up inefficiencies by engaging with their suppliers in relational contracting – informal agreements sustained by the value of future relationships. Our model predicts that countries with a higher level of patience will exhibit greater economic well-being and higher total factor productivity. We provide empirical evidence in line with the predictions of our theory.
Keywords: D23; L14; L22; L23; O10; 330; time preferences; relational contracting; aggregate welfare; TFP